P5.27 INDAPAMIDE SR EFFECTS ON AMBULATORY BRACHIAL AND AORTIC PRESSURE IN HYPERTENSIVE PATIENTS - Y. Kotovskaya; O. Kravtsova; Z. Kobalava (Artery Research, 2013)
Aim: Ambulatory monitoring of central blood pressure (BP) is a new technique for evaluation of antihypertensive drugs efficacy. The aim of the study was to assess changes in ambulatory brachial and central BP after indapamide SR adjunction to treatment regimen in hypertensive patients. Methods: Indapamide SR 1,5 mg was added to 21 hypertensive patients (9 male, age 62 years) with uncontrolled hypertension (clinic BP >140/90 mmHg, 24-h BP >130/80 mmHg and/or daytime BP>135/85 mmHg) after 8 weeks treatment with combination of an ACE inhibitor and a calcium channel blocker. ABPM was done before and after 4 weeks of indapamide SR adjunction with BPLab VASOTENS (“OOO Petr Telegin”, Nizhniy Novgorod, Russia) brachial oscillometric device which allows to derive aortic BP and augmentation index (AIx). Brachial and aortic BP changes were evaluated. p<0,05 was considered significant. Results: Significant (p<0,05) decrease in 24-h, day- and nighttime BP after 4 weeks of indapamide SR adjunction was observed: for brachial systolic pressure, respectively, from 147±13 to 138±10, from 148±13 to 139±10, from 145±15 to 134±14 mmHg, for aortic systolic pressure, respectively, from 137±12 to 128±9, from 137±12 to 128±9, from 137±14 to 126±13 mmHg. AIx@HR75 bpm decreased significantly (p<0,05) also: 24-h AIx from 1,8±24,9 to −11,1±17,5%, daytime AIx from −2,3±25,6 to −15,7±18,1%, night-time from 15,4±21,7 to 1,8±19,5%. Conclusion: Indapamide SR adjunction to combination therapy with combination of an ACE inhibitor and a calcium channel blocker results in significant decrease in brachial and aortic systolic pressure as well as in decrease in aortic pulse pressure augmentation. Decrease in aortic pulse pressure augmentation is observed during both day- and night-time.